Cure Characteristics and Physico-Mechanical Properties of Blends of Epoxidised Natural Rubber and Polystyrene (Biological Sciences - PJSIR, 2006)
Studies in the processing characteristics and physico-mechanical properties of blends of epoxidised natural rubber (ENR) and polystyrene (PS) were carried out using various ratios of their compositions of (100:0, 95:5, 90:10, 85:15, 80:20, 75:25 and 70:30 w/w of epoxidized natural rubber). Epoxidised natural rubber (35% epoxide level) was obtained by reacting natural rubber with peroxyformic generated in situ, using formic acid and hydrogen peroxide. The 35% ENR obtained showed a lower scorch time and cure rates. The blends of ENR with PS (90:10 w/w) showed better physico- mechanical properties in terms of the: tensile strength, elongation at break, hardness, compression set, Plasticity Retention Index (PRI), Mooney viscosity while blends of ENR with PS (95:05 w/w) were very resistance to mineral oil and some organic solvents. However, substitution of ENR with more than 20% of PS showed deleterious effects on the cure characteristics and physico-mechanical behaviour of the vulcanisates.